2020
DOI: 10.1109/tcomm.2019.2959329
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Pair Two-Way Massive MIMO Relaying With Zero Forcing: Energy Efficiency and Power Scaling Laws

Abstract: In this paper, we study a multi-pair two-way half-duplex decode-and-forward (DF) massive multiple-input multiple-output (MIMO) relaying system, in which multiple single-antenna user pairs can exchange information through a massive MIMO relay. For low-complexity transmission, zeroforcing reception/zero-forcing transmission (ZFR/ZFT) is employed at the relay. First, we analytically study the large-scale approximations of the sum spectral efficiency (SE). Furthermore, we focus on three specific power scaling laws… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…More specifically, [13] revealed that by utilizing massive antennas at the base station, the performance loss due to the low-resolution ADCs can be compensated. Further investigations on multipair systems have been recently reported in [9], [14]. In [9], the energy efficiency and power scaling laws of multipair two-way massive MIMO relaying systems with zero-forcing were examined.…”
Section: A Related Workmentioning
confidence: 99%
“…More specifically, [13] revealed that by utilizing massive antennas at the base station, the performance loss due to the low-resolution ADCs can be compensated. Further investigations on multipair systems have been recently reported in [9], [14]. In [9], the energy efficiency and power scaling laws of multipair two-way massive MIMO relaying systems with zero-forcing were examined.…”
Section: A Related Workmentioning
confidence: 99%
“…As per the Multiple Access Broadcast (MABC) protocol [5], the two-way relayed D2D data transmission process is divided into two stages with equal time slots. At the time instant n, all devices transmit signals to the relay simultaneously in the Multiple Access Channel (MAC) phase and the received signal at the relay is given by [6], [9], [11]…”
Section: Signal Transmissionmentioning
confidence: 99%
“…Additionally, supported by Eqns. ( 15)-( 18) and the standard lower capacity bound with the worst-case uncorrelated additive noise [9], the respective…”
Section: A Numerical Expressions Of Spectral Efficiencymentioning
confidence: 99%
See 2 more Smart Citations